Job therapy : finding work that works for you - West, Tessa V. (Portfolio, Penguin, 2024)
"A psychologist's guide to finding your most fulfilling job yet When we're unhappy in our jobs, we often attribute our frustration to a bad manager, boring tasks, and stressful workloads. But our dissatisfaction at work usually stems from a deeper psychological need that's not being met at work, like not getting the recognition you deserve. In Job Therapy, Dr. Tessa West helps you figure out the real reason you're unhappy and shows you how to find a new position in which you'll thrive." -- provider by the publisher